Oligodendrocytes in amyotrophic lateral sclerosis and frontotemporal dementia: the new players on stage - Jamet, Marguerite; Dupuis, Luc; Gonzalez De Aguilar, Jose-Luis (Frontiers in Molecular Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are fatal adult-onset neurodegenerative disorders that share clinical, neuropathological and genetic features, which forms part of a multi-system disease spectrum. The pathological process leading to ALS and FTD is the result of the combination of multiple mechanisms that operate within specific populations of neurons and glial cells. The implication of oligodendrocytes has been the subject of a number of studies conducted on patients and related animal models. In this review we summarize our current knowledge on the alterations specific to myelin and the oligodendrocyte lineage occurring in ALS and FTD. We also consider different ways by which specific oligodendroglial alterations influence neurodegeneration and highlight the important role of oligodendrocytes in these two intrinsically associated neurodegenerative diseases.